PERSEPSI PENGETAHUAN DAN TINGKAT KEPEDULIAN KOMUNITAS PETANI KOPI TERHADAP PELESTARIAN KAWASAN TAMAN NASIONAL KERINCI SEBLAT - Anggri Puspita Sari; Praningrum Praningrum (Unib Press Universitas Bengkulu, 2019)
This study aims to determine how the perception of knowledge and level of concern of the coffee farmers community towards the preservation of the Kerinci Seblat National Park (TNKS) District of Lebong. This study uses qualitative or naturalistic methods because they are carried out in natural conditions. Data collection methods through Hand Delivery using questionnaires and interviews.The sample in study is the coffee farming community formed in the KUB “Maju Lestari. While data analysis is carried out simultaneously with the process of collecting data (on going analysis) using qualitative descriptive methods. It is hoped that through this approach, researchers will be able to develop new hypotheses specifically related to the behavior of the coffee farmers community in Suka Negeri Village, Topos District, Lebong Regency. From a practical aspect, the basic data that has been collected, analyzed and expected to be formulated in a form or method in the policy of developing and developing a community of coffee farmers (community development), especially in the TNKS area of Lebong Regency